Use of long acting injectable aripiprazole before and through pregnancy in bipolar disorder: a case report - Isabel Ballester-Gracia; Miriam Pérez-Almarcha; Ana Galvez-Llompart; Miguel Hernandez-Viadel (BMC, 2019)
Abstract Background Long-acting injectable (LAI) antipsychotics for psychotic disorders provide advantages in treatment compliance, but data on their use in pregnancy are very limited. We present a clinical case of aripiprazole LAI use in pregnancy. Case presentation A 43-year-old woman diagnosed with bipolar disorder, with several relapses due to treatment interruption while trying to conceive. Finally, aripiprazole LAI treatment was planned by mutual agreement between doctor and the patient, who took aripiprazole LAI before and during pregnancy. She gave birth at 40 weeks to a 3500 g baby girl with no congenital malformations, who was healthy at 5 months after delivery. Conclusion As far as we know, this is the first case report on aripiprazole LAI use during pregnancy. Although we exercise caution in drawing conclusions from a single case, and each case should be weighed up individually, aripiprazole LAI could be a therapeutic option in similar circumstances.